Antimalarial Properties of Streptomyces hygroscopicus subsp Hygroscopicus Secondary Metabolite Active Fractions: In Silico and In Vivo Analysis - Loeki E Fitri, - (Advanced Scientific Research, 2021)
Background: Crude extract of Streptomyces hygroscopicus has antimalarial effect in vivo and its active fractions showed Plasmodium inhibition in vitro. This study aims to analyze the antimalarial activity of fraction 41 and 44 of S.hygroscopicus in vivo and predict their antimalarial mechanism in silico. Material and methods: Secondary metabolite of S.hygroscopicus was identified using LC/MS. In silico analysis was done using PfA-M1, Falcipain 2 protease, and PfCRT as protein targets from PDB and active compound ligand from PubChem. The pharmacokinetic analysis was done using SwissADME. In vivo study was conducted using Plasmodium berghei infected mice that divided into 1 positive control group, 1 Artesunate group, and 8 treatment groups that administrated with fraction 41 and 44 each in dose 8,125 µg/kgBW, 32,5 µg/kgBW, 130 µg/kgBW, and 520 µg/kgBW. Result: Tryptanthrin was identified from S.hygroscopicus. Tryptanthrin has fulfilled drug-likeness criteria and stronger binding affinity to PfA-M1, Falcipain 2 protease, and PfCRT than control ligand. Fraction 41 showed a significant difference in parasite density between positive control group and 130µg/kgBW group (p=0.046) as well as 520µg/kgBW group (p=0.004). Fraction 44 showed a significant difference in parasite density between positive control group and 130µg/kgBW group (p=0.024) as well as 520µg/kgBW group (p=0.004). Correlation test of fraction 41 showed a strong negative relationship between doses and parasite density on day 3 (p=0.001; r=-0.607) and day 4 (p=0.000; r=-0.700) as well as fraction 44 on day 3 (p=0.044; r=-0.589). Conclusion: Active fractions of Streptomyces hygroscopicus subsp Hygroscopicus that contained Tryptanthrin has a potential antimalarial agent.